Trimethylsilyl Trifluoromethanesulfonate-Promoted Cyclocondensation of β-Ketoenamides and Subsequent Nonaflation to Pyrid-2-yl and Pyrid-4-yl Nonaflates as Flexible Precursors for Polysubstituted Pyridines - Hommes, Paul; Berlin, Sarah; Reissig, Hans-Ulrich (Synthesis, 2013)
The intramolecular condensation of β-ketoenamides to 2- and/or 4-pyridone derivatives using either KOt-Bu or trimethylsilyl trifluoromethanesulfonate/Hünig’s base was investigated. Subsequent nonaflation of the cyclization products allowed a facile purification and further functionalization through Suzuki–Miyaura couplings leading to new highly substituted pyridine derivatives. The dependence of the regioselectivity of cyclocondensation on the structure of the β-ketoenamides is discussed.
Keywords: enamides; pyridines; cyclocondensation; nonaflates; cross couplings